The Effect of Probe Pressure on In Vivo Single Fiber Reflectance Spectroscopy - Shakibaei, Ali Akbar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Reflectance spectroscopy is a method to noninvasively quantitate the scattering and absorption properties of a turbid medium like tissue. The absorption and scattering properties can be used in diagnosis of different diseases such as cancer. Dependence of the acquired spectra to the environmental and physiological factors like probe pressure and habits of the person are being sought out in this thesis. Our applied method, single fiber reflectance (SFR) spectroscopy, uses a single fiber for delivery and detection of the visible light. The SFR spectrum can be fitted by a nonlinear model of the scattering and absorption properties of the tissue under investigation. In this study, SFR measurements are made by a fiber-optic probe gently placed on the lip tissue of some volunteers. The effect of variation in the probe pressure during the measurements is evaluated through the probable change in the extracted parameters from the fitted spectra. In order to do this, first the most appropriate model for the human lip reflectance spectrum is found. Then, the variation in the extracted parameters due to different probe pressures or physiologic characteristics of the volunteers is investigated. Keywords: reflectance spectroscopy - single fiber reflectance spectroscopy. ………………………………………………………………………………………………………………………… ÖZ: Yansıtma Spektroskopisi, doku gibi bulanık bir ortamın saçılma ve soğurma özelliklerini non invaziv bir şekilde niceleştiren bir yöntemdir. Soğurma ve saçılma özellikleri, kanser gibi çeşitli hastalıkların teşhisinde kullanılabilir. Bu tezde, elde edilen spektrumun prob baskısı ve kişinin alışkanlıkları gibi çevresel ve fizyolojik faktörlere bağlı olup olmadığı aranmaktadır. Uyguladığımız yöntem olan Tek Fiber Yansıma (SFR ) Spektroskopisi, görünür ışık iletimi ve saptanması için tek bir fiber kullanmaktadır. SFR spektrumu, araştırmakta olduğumuz dokunun saçılma ve soğurma özelliklerinin doğrusal olmayan bir modeli ile incelenebilir. Bu çalışmadaki SFR ölçümler, bazı gönüllülerin dudak dokularının üzerine yavaşça yerleştirilen bir fiber -optik prob ile yapılmıştır. Ölçümler boyunca gerçekleşen prob basıncındaki değişimlerin etkisi, grafiklerden elde edilen parametrelerin olası değişimleri dikkate alınarak değerlendirilmiştir. Bunu yapabilmek için öncelikle insan dudak yansıtma spektrumuna en uygun model bulunur. Son olarak, parameterler üzerinde, farklı prob baskılarına bağlı olarak veya gönüllülerin fizyolojik özellikleri nedeniyle ortaya çıkan variyasyonlar incelenmiştir. AnahtarKelimeler: yansıma spektroskopisi, tek fiber yansıma spektroskopisi.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2014. Supervisor: Prof. Dr. Özay Gürtuğ.
Keywords: Physics; reflectance spectroscopy - single fiber reflectance spectroscopy